High-throughput measurement of 25-hydroxyvitamin D by LC–MS/MS with separation of the C3-epimer interference for pediatric populations - El-Khoury, Joe (2016)
Background Liquid chromatography–tandem mass spectrometry (LC–MS/MS) is widely used for the measurement of 25-hydroxyvitamin D3 (25OHD3) and 25-hydroxyvitamin D2 (25OHD2) in blood. However, the presence of 25OHD3 C3-epimer (3-epi-25OHD3) may cause interference and overestimation of the 25OHD3 level. We developed a rapid and simple assay for measurement of 25OHD that separates this interference and to investigate its impact on 25OHD3 measurement in adult and pediatric populations. Methods Sample preparation consisted of protein precipitation followed by solid-phase extraction with an LC run time of 4.8 min. Method comparison with another LC–MS/MS method of a major reference laboratory that does not separate the C3-epimer interference was performed using adult (n = 52) and pediatric (n = 40) samples. Results This method is free from significant ion suppression, carryover and interference. The assay can separate 25OHD3 from the 3-epi-25OHD3, and can measure 25OHD2 and 25OHD3 from 4.2 to 310.7 ng/ml and 5.2 to 311.1 ng/ml, respectively. Method comparison with a LC–MS method that does not separate the interference revealed biases of − 0.15 and 4.54 for 25OHD3 measurement in adult and pediatric samples, respectively. Conclusion A fast and simple LC–MS/MS method for quantification of 25OHD3 and 25OHD2 without 3-epi-25OHD3 interference was developed. This assay is required for accurate quantitation of 25OHD3 in pediatric samples and suitable for routine use in a high volume clinical laboratory.